Dipole-Based Wavelet Superposition for Accurate Design and Analysis of Metasurface - Hongjun Chu; Jiaran Qi; Jinghui Qiu (IEEE Photonics Journal)
Design and analysis of metasurface-based devices mainly rely on the ideal ray theory and full-wave simulation technique. However, for near-field and low-frequency applications, these idealized design and time-consuming full-wave simulation methods often suffer from inaccuracy and inefficiency, which hinders the rapid prototyping and further evolution of metasurface-based devices. Here, dipole-based wavelet superposition (DWS) is proposed and formulated to accurately and efficiently design the metasurface and analyze its diffraction field, by treating unit cell on the metasurface and every wavefront representing the target field as Hertzian dipole. We further define quantitatively an effective zone, within which the proposed DWS offers sufficiently accurate results comparable to the full-wave simulation. A series of numerical experiments on design and analysis of metasurface are then carried out to validate our DWS method. Excellent and more superior consistence with the full-wave analysis and theoretical results confirms that the DWS method provides an advanced closed-loop design and analysis tool with significantly improved accuracy and efficiency for metasurface-based devices.